O-GlcNAcylation and Metabolic Reprograming in Cancer - Jóźwiak, Paweł; Forma, Ewa; Bryś, Magdalena; Krześlak, Anna (Frontiers in Endocrinology, 2014)
Although cancer metabolism has received considerable attention over the past decade, our knowledge on its specifics is still fragmentary. Altered cellular metabolism is one of the most important hallmarks of cancer. Cancer cells exhibit aberrant glucose metabolism characterized by aerobic glycolysis, a phenomenon known as Warburg effect. Accelerated glucose uptake and glycolysis are main characteristics of cancer cells that allow them for intensive growth and proliferation. Accumulating evidence suggests that O-GlcNAc transferase (OGT), an enzyme responsible for modification of proteins with N-acetylglucosamine, may act as a nutrient sensor that links hexosamine biosynthesis pathway to oncogenic signaling and regulation of factors involved in glucose and lipid metabolism. Recent studies suggest that metabolic reprogramming in cancer is connected to changes at the epigenetic level. O-GlcNAcylation seems to play an important role in the regulation of the epigenome in response to cellular metabolic status. Through histone modifications and assembly of gene transcription complexes, OGT can impact on expression of genes important for cellular metabolism. This paper reviews recent findings related to O-GlcNAc-dependent regulation of signaling pathways, transcription factors, enzymes and epigenetic changes involved in metabolic reprogramming of cancer.